Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan Pada PT. XXX - Yuliyanti Nur Hikmah; Irwin Ananta Vidada (STIKes Ibnu Sina Ajibarang, 2024)
PT.XXX is one of the companies in cikarang engaged in Electrical Supply and Maintenance Service that has many projects in various regions of Indonesia. To be able to know what influences can affect the resulting performance. Then the company also needs to know whether the motivation that has been given has an effect on performance and whether work discipline is prioritized in carrying out work. The research method used is a quantitative statistical method by doing reset and questionnaires to collect data. In this writing using analytical techniques consisting of several multicollinearity test that get the value of 2.286 < 10 which means that the regression model does not occur multicollinearity problem, Hetereskeasticity test that produces images with point spread which means that the regression model can be used, normality test that produces the value of sig 0.127 > 0.05 which shows that normality is met. Multiple Linear regression test results in the value of Y=11.916 – 0.002 + 0.571 which shows that motivation and discipline are constant motivation variable if having an increase of 1 will decrease by -0.002 in the discipline variable will increase by 0.571, the T test shows that motivation does not affect performance while discipline affects performance, the F test shows that the independent variable together affect the dependent variable, the coefficient of determination test shows that the value of R 0.599 which means it is quite strong and the value of R square is 0.359 which shows that 35.9% is influenced by motivation and discipline.